Pengaruh Tepung Sagu dan Kacang Merah terhadap Kadar Protein dalam Pembuatan Nastar - Harni Sepriyani (Jurnal Penelitian Farmasi Indonesia, 2020)
Local food potential in Indonesia is very abundant, including cereals, palmae, tubers that thrive in almost all regions of Indonesia. Sago flour for making pastries (nastar) is rich in carbohydrates (starch) but is very low in other nutrients, especially protein content. Therefore, sago flour needs to be added with protein foods such as red beans. Red beans have a high enough protein content, red beans are made of flour and are used as additional ingredients in making pastries. In the study, a comparison of sago flour and red bean flour used was 25% sago flour: 75% red bean flour, 50% sago flour: 50% red bean flour, 75% sago flour: 25% kidney bean flour and 100% sago flour. . The results showed that the protein content was 4.51% - 9.38%.